Perovskite thin film modified by lead nitrate interface, solar cell and preparation method of perovskite thin film

CN119744035AInactive Publication Date: 2025-04-01HUAQIAO UNIVERSITY
5 Cites 0 Cited by

Patent Information

Application Number
CN202510244932.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-04
Publication Date
2025-04-01
Estimated Expiration
Not applicable · inactive patent

Smart Images

  • Figure CN119744035A_ABST
    Figure CN119744035A_ABST
Patent Text Reader

Abstract

The invention provides a lead nitrate interface modified perovskite thin film, a solar cell and a preparation method thereof, and belongs to the technical field of semiconductor devices. The preparation method of the solar cell comprises the following steps: S1, pretreating a conductive transparent substrate; s2, preparing an electron transport layer: depositing a TiO2 thin film on the surface of the conductive transparent substrate to form the electron transport layer; s3, preparing a perovskite layer: spin-coating a PbBr2 solution on the electron transport layer, and then spin-coating a CsBr solution to form the perovskite layer; s4, preparing a Pb (NO3) 2 modified layer: spin-coating a Pb (NO3) 2 solution on the perovskite layer to form the Pb (NO3) 2 modified layer; and S5, preparing an electrode: coating the surface of the perovskite layer with a carbon electrode. The Pb (NO3) 2 is introduced to the perovskite layer, so that the long-term stability of the perovskite layer can be improved, and the photovoltaic performance of the perovskite solar cell is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a lead nitrate interface-modified perovskite film, a solar cell and a preparation method thereof, and belongs to the technical field of semiconductor devices. Background Art

[0002] Perovskite solar cells (PSCs) have become a hot topic in the field of solar technology due to their excellent photovoltaic conversion efficiency, simple production process, significant light absorption ability, long carrier diffusion distance, adjustable band gap, and a remarkable photovoltaic conversion efficiency of up to 26.7% achieved in a decade of research. Among the various perovskite solar cells, organic-inorganic hybrid PSCs have achieved significant improvements in power conversion efficiency (PCE) and have become the leaders in this field. However, they have encountered major obstacles in the commercialization process due to the inherent instability of organic components, which are prone to decomposition in humid and high temperature environments and when in contact with air. Among the various cesium-based all-inorganic PSCs, CsPbBr3 materials have shown good light harvesting performance and excellent stability under standard environmental conditions. At the same time, it also has high electron mobility and long electron lifetime, so it is widely considered to be an ideal choice in the field of perovskite solar cells.

[0003] Although researchers in the field of perovskite solar cells have conducted a lot of research work, the conversion efficiency of CsPbBr3-PSC has not yet caught up with the level of other hybrid perovskite materials. During the annealing process of perovskite solar cells, the generation of interface defects will capture a portion of the free charges, which will destroy the photophysical properties of the cell and lead to performance degradation. Although shallow energy level defects may cause some energy loss because they can capture charges, these charges may still be re-excited; however, deep energy level defects will lead to serious non-radiative recombination phenomena, which will significantly reduce the performance of perovskite solar cells. Therefore, how to further improve the performance of inorganic PSCs while ensuring high stability is still a key issue that needs to be solved urgently. Summary of the invention

[0004] The present invention provides a lead nitrate interface-modified perovskite film, a solar cell and a preparation method thereof, which can effectively solve the above-mentioned problems.

[0005] The present invention is achieved in that: A lead nitrate interface modified perovskite film is provided. A Pb(NO3)2 solution is spin-coated on a perovskite layer to form a Pb(NO3)2 modified layer, namely the lead nitrate interface modified perovskite film.

[0006] In some embodiments, the spin coating has a rotation speed of 1800-2200 rpm and a time of 25-35 s.

[0007] In some embodiments, the spin coating is followed by annealing at 240-260° C. for 4-10 min.

[0008] In some embodiments, the Pb(NO3)2 solution is a Pb(NO3)2 / triethyl phosphate (TEP) solution with a concentration of 0.25-3.0 mg / mL.

[0009] A lead nitrate interface-modified perovskite solar cell adopts the lead nitrate interface-modified perovskite film.

[0010] A method for preparing a lead nitrate interface-modified perovskite solar cell comprises the following steps: S1, pretreatment of conductive transparent substrate; S2. Preparing an electron transport layer: depositing a TiO2 thin film on the surface of a conductive transparent substrate to form an electron transport layer; S3, preparing a perovskite layer: first spin-coating a PbBr2 solution on the electron transport layer, and then spin-coating a CsBr solution to form a perovskite layer; S4, preparing a Pb(NO3)2 modified layer: spin coating a Pb(NO3)2 solution on the perovskite layer to form a Pb(NO3)2 modified layer; S5. Prepare an electrode: coat a carbon electrode on the surface of the perovskite layer.

[0011] In some embodiments, step S2 is specifically as follows: depositing a 1-4 v / v% TiCl4 aqueous solution on the surface of a conductive transparent substrate at 65-75°C for 25-35 minutes, then heating to 75-85°C and continuing to deposit for 10-15 minutes, standing until the temperature drops to room temperature, successively immersing in deionized water and ethanol for cleaning, and drying, the drying speed is 3950-4050r / min, the time is 25-35s, heating at 95-105°C for 4-10 minutes, and finally calcining at 450-550°C for 50-70 minutes to obtain an electron transport layer.

[0012] In some embodiments, step S3 is specifically as follows: evenly spreading a 0.2-0.5 g / mL PbBr2 DMF solution on the prepared electron transport layer, spin coating at a rotation speed of 1800-2200 rpm for 28-32 s, and then annealing at 90-110°C for 25-35 min to form a PbBr2 film; then, spin coating a CsBr solution on the PbBr2 film at a rotation speed of 1800-2200 rpm, and then annealing at 240-260°C for 4-10 min to obtain the final perovskite layer.

[0013] In some embodiments, step S4 is specifically as follows: evenly spreading the TEP solution of Pb(NO3)2 on the perovskite layer, spin coating at a rotation speed of 1800-2200 rpm for 25-35s, and then annealing at 240-260°C for 4-10min to obtain a Pb(NO3)2 modified layer.

[0014] In some embodiments, step S5 is specifically: coating the carbon paste by screen printing, and then heating at 110-130° C. for 10-20 min to prepare a carbon electrode.

[0015] In some embodiments, in step S1, the conductive transparent substrate is a FTO conductive glass substrate.

[0016] In some embodiments, in step S1, the pretreatment is to use laser to etch the conductive transparent substrate so that both sides thereof are non-conductive areas.

[0017] The beneficial effects of the present invention are: In the present invention, Pb(NO3)2 is used as a modifier. This strategy effectively promotes the formation of CsPbBr3 phase by passivating the defects in the perovskite layer. This process significantly improves the crystal quality of the perovskite film, making the film have fewer grain boundaries and defects. Such improvements are of great significance for reducing the recombination of carriers inside perovskite solar cells, thereby significantly enhancing the photovoltaic performance of perovskite solar cells. The introduction of Pb(NO3)2 not only optimizes the energy level arrangement of perovskite solar cells, but also significantly reduces the density of interface defect states, which further improves the extraction and transmission efficiency of carriers and effectively inhibits charge recombination.

[0018] The present invention obtains a perovskite thin film battery by a spin coating preparation method, and its final carrier recombination lifetime is significantly increased, successfully achieving the suppression of charge recombination and the enhancement of charge extraction. Finally, through the preparation of the above steps, a perovskite solar cell that is both efficient and stable is obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0020] Figure 1 This is a structural diagram of a perovskite solar cell modified with lead nitrate interface according to an embodiment.

[0021] Figure 2: are SEM images of CsPbBr3 thin films, wherein (a), (b), (c) and (d) are SEM images of the CsPbBr3 thin films of the comparative example and embodiments 1, 2 and 3, respectively.

[0022] Figure 3 JV curves of the lead nitrate interface-modified perovskite solar cells of the comparative example and examples 1, 2 and 3.

[0023] Figure 4 This is the environmental stability diagram of the lead nitrate interface modified perovskite solar cell of the comparative example and Example 2. DETAILED DESCRIPTION

[0024] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention. Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the invention claimed for protection, but merely represents the selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0025] In an embodiment of the present invention, a method for interface-modified perovskite film by lead nitrate is proposed. Specifically, the method involves spin-coating a layer of Pb(NO3)2 solution on the surface of the perovskite layer to form a layer of Pb(NO3)2 modified layer. This layer of perovskite film interface-modified by lead nitrate can effectively improve the performance of the film. In an embodiment of the present invention, Pb(NO3)2 is used as a modifier, which can effectively passivate the defects in the perovskite layer. Through this passivation, the formation of CsPbBr3 phase is promoted, thereby improving the crystal quality of the perovskite film. Since the modified perovskite film has fewer grain boundaries and defects, the recombination phenomenon of carriers inside the perovskite solar cell can be significantly reduced. This improvement directly enhances the photovoltaic performance of the perovskite solar cell, so that it exhibits higher efficiency and stability in practical applications.

[0026] In some embodiments, the spin coating has a rotation speed of 1800-2200 rpm and a time of 25-35 s.

[0027] In some embodiments, the spin coating is followed by annealing at 240-260° C. for 4-10 min.

[0028] In some embodiments, the Pb(NO3)2 solution is a Pb(NO3)2 / triethyl phosphate (TEP) solution with a concentration of 0.25-3.0 mg / mL. By using a solution in this specific concentration range, the performance of the battery is significantly improved.

[0029] The embodiment of the present invention provides a lead nitrate interface-modified perovskite solar cell, which adopts the lead nitrate interface-modified perovskite film.

[0030] The embodiments of the present invention aim to provide a method for preparing a perovskite solar cell with interface modification by lead nitrate, which comprises a series of detailed steps to ensure the performance and efficiency of the final product.

[0031] S1. First, pre-treat the conductive transparent substrate. This step is the basis of the entire preparation process and ensures that the subsequent layers can be well attached to the substrate. S2. The next step is the key step of preparing the electron transport layer: on the surface of the pre-treated conductive transparent substrate, the electron transport layer is formed by depositing a TiO2 film. This step is crucial to the electron transport efficiency. S3. Next, prepare the perovskite layer: on the already formed electron transport layer, first spin-coat the PbBr2 solution, then spin-coat the CsBr solution, and through the interaction of the two solutions, form the desired perovskite layer, which is the core part of the solar cell; S4, then prepare the Pb(NO3)2 modified layer: spin-coat the Pb(NO3)2 solution on the perovskite layer. Through the modification of this solution, the interface characteristics of the perovskite layer can be further optimized, thereby improving the performance of the entire solar cell; S5. The last step is to prepare the electrode: coating the carbon electrode on the surface of the perovskite layer. After this step is completed, the entire solar cell preparation process is basically completed. What remains is to test and evaluate the battery.

[0032] In some embodiments, step S2 specifically includes the following operations: First, a TiCl4 aqueous solution with a concentration of 1-4 v / v% is deposited on the surface of a conductive transparent substrate under the condition of controlling the temperature at 65-75°C, and this process lasts for 25-35 minutes. Then, the temperature is raised to 75-85°C, and the deposition is continued for about 10-15 minutes. After the deposition is completed, the substrate is allowed to stand until the temperature naturally drops to room temperature. Subsequently, the substrate is immersed in deionized water and ethanol for thorough cleaning to remove residual chemicals. After cleaning, the liquid on the substrate is dried using a spin dryer, and the speed during drying is set at 3950-4050rpm, and the drying time is controlled at 25-35s. After drying, the substrate is placed in an environment of 95-105°C and heated for 4-10 minutes to further remove residual solvents and moisture. Finally, the substrate is calcined at a high temperature of 450-550°C for 50-70 minutes. Through this series of processing steps, the desired electron transport layer is finally obtained.

[0033] In some specific embodiments, step S3 can be described in detail as follows: First, prepare a DMF solution of PbBr2 with a concentration in the range of 0.2-0.5g / mL. Then, the solution is evenly coated on the surface of the electron transport layer that has been prepared in advance. Next, a spin coater is used to perform a spin coating operation at a rotation speed of 1800-2200rpm for a duration of 28-32s. After the spin coating is completed, the substrate coated with the PbBr2 solution is placed in an oven at 90-110°C for annealing, and the annealing time lasts for 25-35min to form a uniform PbBr2 film. Next, the CsBr solution is evenly spin-coated on the already formed PbBr2 film, and a rotation speed of 1800-2200rpm is also used during spin coating, and the spin coating time is kept consistent. After the spin coating is completed, the substrate is placed in a high temperature environment of 240-260°C for annealing, and the annealing time is controlled at 4-10min. Through this series of operations, the desired perovskite layer is finally obtained.

[0034] In certain specific embodiments, step S4 can be described in detail as follows: First, a certain amount of Pb(NO3)2 is dissolved in a TEP (triethylene glycol monomethyl ether) solvent to form a uniform solution. Next, the solution is evenly spread on the formed perovskite layer, and the spin coating operation is performed at a speed of 1800 to 2200 rpm using a spin coating technique for 25 to 35 seconds. After the spin coating is completed, the sample is placed in a heat treatment environment at a temperature of 240 to 260°C for annealing, and the annealing time lasts for 4 to 10 minutes. Through this series of operations, a uniform Pb(NO3)2 modified layer is finally formed on the perovskite layer.

[0035] In some other embodiments, step S5 can be described in detail as follows: using screen printing technology to uniformly coat the carbon paste material on a specific substrate. After coating, the substrate coated with the carbon paste is placed in a heat treatment environment at a temperature of 110 to 130° C. for heating for a duration of 10 to 20 minutes. Through such a heating process, the carbon paste can be effectively solidified to prepare the desired carbon electrode. This carbon electrode has good electrical conductivity and mechanical stability and is suitable for a variety of electronic devices.

[0036] In some embodiments, in step S1, the conductive transparent substrate is a FTO conductive glass substrate.

[0037] In some embodiments, in step S1, the pretreatment is to use laser to etch the conductive transparent substrate to form non-conductive areas on both sides, and then use glass cleaning liquid, deionized water, and ethanol ultrasonic cleaning respectively, and use ultraviolet ozone cleaning machine before use.

[0038] Example 1 A method for preparing a perovskite solar cell based on a lead nitrate (Pb(NO3)2) interface modification method comprises the following steps: S1. Pretreatment of FTO conductive glass: FTO conductive glass (1.5 cm × 1.5 cm) was ultrasonically cleaned for 20 min with glass cleaning solution, deionized water, and ethanol, respectively. It was treated with a UV ozone cleaner for 20 min before use.

[0039] Specifically, before cleaning, the FTO conductive glass must be placed under a laser etcher, and the laser etcher is used to etch both sides of the FTO glass into non-conductive areas.

[0040] S2. Preparation of electron transport layer: Prepare 400ml of TiCl4 / H2O solution with a volume ratio of 9:400, deposit at 70℃ for 30min, then heat to 80℃ and continue to deposit for 13min. Let it stand until the temperature drops to room temperature. Immerse in deionized water and ethanol for cleaning, and finally use a sizing machine to spin dry the glass. The parameters are set to 4000r / min, 30s, 2000r / s (acceleration). Place the dried glass on a heating table and heat at 100℃ for 5min. Finally, place the glass in a crucible, seal it with tin foil and place it in a muffle furnace for calcination at 500℃ for 1h to obtain an electron transport layer.

[0041] Specifically, the method for preparing the TiCl4 solution is to put 400 mL of deionized water in a clean beaker and put it in the refrigerator until the water temperature drops to 0°C. Then take it out and slowly drip 9 mL of analytically pure TiCl4 solution in an ice water bath with stirring. Make sure that the prepared TiCl4 solution is colorless and transparent. After preparation, put it in the refrigerator for use.

[0042] S3, preparation of perovskite layer: use a pipette to take 100μL PbBr2 / N,N-dimethylformamide (DMF) solution, evenly spread it on the prepared electron transport layer, spin-coat it at 2000rpm for 30s, and then anneal it on a 100℃ heating table for 30min to form a PbBr2 film. Next, spin-coat 120μL of CsBr solution on the PbBr2 film at 2000rpm for 15s, and anneal it at 250°C for 15min after spin coating to obtain the final perovskite layer.

[0043] To further remove the possible residual solvent on the surface of the perovskite solar cell, an isopropanol solution was spin-coated on the perovskite layer, and the spin-coating parameters remained unchanged. After the spin-coating, the perovskite solar cell was placed on a hot stage and annealed at 250°C for 5 minutes.

[0044] Specifically, the preparation method of PbBr2 solution is to weigh 7.38g of lead bromide solid into a 20mL glass bottle in a glove box, then add 20mL of N,N-dimethylformamide (DMF) into the glass bottle, place it on a 75℃ heating table and stir until dissolved. After use, store it at room temperature and seal it with polymer glue.

[0045] Specifically, the preparation method of CsBr solution is to weigh 2.5 g CsBr into a glass bottle in a weighing room, then add 10 mL of deionized water, and shake at room temperature to dissolve.

[0046] S4. Preparation of Pb(NO3)2 modified layer: Prepared Pb(NO3)2 / triethyl phosphate (TEP) solution for use, draw 100 μL of solution with a pipette, spread it evenly on the perovskite layer, spin coat at 2000 rpm for 30 s, and then anneal on a heating table at 250 °C for 5 min to obtain a Pb(NO3)2 modified layer.

[0047] For the target perovskite solar cell, a 10 mg / mL Pb(NO3)2 / TEP solution was first prepared, diluted to a 0.5 mg / mL concentration solution as required, and spin-coated with the same parameters to obtain a Pb(NO3)2 modified layer.

[0048] The preparation method of Pb(NO3)2 solution is as follows: weigh 100 mg of Pb(NO3)2 solid into a glass bottle in a weighing room, and then add 10 mL of triethyl phosphate (TEP) into the glass bottle to make a 10 mg / mL Pb(NO3)2 solution for standby use.

[0049] S5. Preparation of electrode: Coat the carbon paste by screen printing, and transfer the film to a hot plate at 120°C and heat for 15 min to prepare a carbon electrode.

[0050] The specific steps of the screen printing method are as follows: During the carbon brushing process, the humidity and temperature of the environment are maintained at 30%-40% humidity and 20℃-25℃. Use the prepared edge wiping liquid to wipe 3-4mm of perovskite in the direction perpendicular to the FTO conductive glue, and also wipe the back of the battery clean. After all the battery edges are wiped, 15 batteries are grouped together and aligned under the screen template. Apply an appropriate amount of carbon paste on the top of the carbon brushing area of ​​the screen, and then use a scraper to brush the carbon paste up and down twice to ensure that the carbon paste is evenly applied to the perovskite solar cell.

[0051] The preparation method of the edge wiping liquid is as follows: dimethyl sulfoxide (DMSO) and methanol are mixed in a volume ratio of 1:9 to prepare the perovskite edge wiping liquid, and the mixture is allowed to stand at room temperature for use.

[0052] This embodiment is based on the method of preparing a perovskite solar cell by lead nitrate (Pb(NO3)2) interface modification method. The perovskite solar cell includes a conductive transparent substrate, an electron transport layer, a perovskite layer, a Pb(NO3)2 modification layer and a carbon electrode arranged in sequence.

[0053] Example 2 The preparation method in steps S1, S2, S3 and S5 of Example 2 is the same as that in Example 1, except that: for the target perovskite solar cell in S4, a 10 mg / mL Pb(NO3)2 / TEP solution is first prepared, diluted to a solution with a concentration of 1.0 mg / mL as required, and spin-coated with the same parameters to obtain a Pb(NO3)2 modified layer.

[0054] Example 3 The preparation method in steps S1, S2, S3 and S5 of Example 3 is the same as that in Example 1, except that: for the target perovskite solar cell in S4, a 10 mg / mL Pb(NO3)2 / TEP solution is first prepared, diluted to a solution with a concentration of 2.0 mg / mL as required, and spin-coated with the same parameters to obtain a Pb(NO3)2 modified layer.

[0055] Comparative Example The preparation method in steps S1, S2, S3 and S5 of the comparative example is the same as that in Example 1, except that there is no step S4.

[0056] Please refer to Figure 1As shown, a schematic diagram of the structure of a perovskite solar cell of a specific embodiment is shown. The layers arranged from bottom to top include: 1. A conductive transparent substrate, which provides the necessary conductivity for the cell while maintaining transparency; 2. An electron transport layer, which is responsible for efficiently transmitting electrons; 3. A perovskite layer, which is the core of the solar cell and is responsible for absorbing sunlight and converting it into electrical energy; 4. A Pb(NO3)2 modification layer, which protects and modifies the perovskite layer to improve the stability and efficiency of the cell; and 5. A carbon electrode, which serves as the upper electrode of the cell and collects and conducts the generated current.

[0057] Performance Testing 1. SEM characterization method: Field emission scanning electron microscopy (SEM) technology was used to carefully characterize and analyze the surface morphology of the perovskite layer by setting the acceleration voltage to 5.0 kV and the magnification to 20,000 times. This method can provide detailed information about the surface microstructure of the material and help understand the surface characteristics of the perovskite material.

[0058] 2. JV characteristic curve and stability test method of perovskite solar cells: The test is carried out under the irradiation of AM1.5G standard simulated light source (Newport, PVIV-94043A) with a light intensity of 100W / m, using Keithley-2400 standard system. In this way, the current-voltage (JV) characteristic curve of perovskite solar cells under standard test conditions can be obtained, and then its performance and stability can be evaluated.

[0059] See also Figure 2 , (a), (b), (c), and (d) show the SEM images of the CsPbBr3 thin films of the comparative example and Examples 1, 2, and 3, respectively. By comparison, it can be clearly seen that the grain size of the film modified with Pb(NO3)2 has increased significantly compared with the comparative example. This phenomenon shows that the modification of Pb(NO3)2 has a positive effect on improving the crystal quality of the perovskite film.

[0060] observe Figure 2 (c) in Example 2 shows that the average grain diameter of the perovskite film reaches 1056.9 nm and exhibits high uniformity. This result is significantly improved compared to the unmodified blank group (average grain size is 660.2 nm). The increase in grain size and uniformity usually means that the film has fewer grain boundaries and defects, which can significantly reduce the recombination of carriers inside the perovskite solar cell and enhance the electrical performance of the cell.

[0061] Look again Figure 2In (d), in Example 3, the grain size is reduced and the variability is increased. Generally, the increase in grain size and the improvement in uniformity indicate that the crystal quality of the film is improved. This usually means that the film has fewer grain boundaries and defects, which can significantly reduce the recombination of carriers inside the perovskite solar cell and enhance the electrical properties of the perovskite solar cell. However, in Example 3, the reduction in grain size and the increase in variability may indicate that excessive Pb(NO3)2 modification has an adverse effect on the crystal quality of the film.

[0062] See also Figure 3 , and the JV curves of the perovskite solar cells of the comparative ratio and Example 1, Example 2, and Example 3 are compared. The results show that the concentration of Pb(NO3)2 has a significant effect on the photovoltaic performance, among which the concentration corresponding to Example 2 is the best. At this time, the photoelectric conversion efficiency (PCE) of the perovskite solar cell reaches 10.55%, and other photovoltaic parameters such as open circuit voltage (Voc), short circuit current density (Jsc) and fill factor (FF) also perform well. This shows that an appropriate amount of Pb(NO3)2 can effectively passivate the defects of CsPbBr3 film, improve the phase purity of CsPbBr3, and promote the extraction and transmission of holes.

[0063] However, if the concentration of Pb(NO3)2 is too high, it will cover the perovskite surface and hinder the transport of carriers, which will lead to a decrease in the photoelectric conversion efficiency (PCE). Therefore, choosing the right Pb(NO3)2 concentration is crucial to optimizing the performance of perovskite solar cells.

[0064] See also Figure 4 , the environmental stability diagram of the comparative example and Example 2. In order to evaluate its stability, the perovskite solar cell was placed in a normal environment and a 30-day stability test was performed. The results show that compared with the perovskite solar cell in the comparative example, the cell in Example 2 has been significantly improved in terms of stability. This shows that by appropriate Pb(NO3)2 modification, the environmental stability of perovskite solar cells in practical applications can be effectively improved, thereby extending their service life.

[0065] The performance tests of the perovskite solar cells of Examples 1, 2, 3 and the comparative example are shown in Table 1.

[0066] Table 1

[0067] Table 1 lists in detail the performance parameters of perovskite solar cells under different experimental conditions. These parameters include VOC (open circuit voltage), JSC (short circuit current density), FF (fill factor) and PCE (photovoltaic conversion efficiency). By comparing these key indicators, the impact of different experimental schemes on battery performance can be intuitively evaluated.

[0068] In Table 1, it can be seen that compared with the control group, Examples 1, 2 and 3 have achieved significant improvements in key performance indicators such as VOC, JSC, FF and PCE. In particular, Example 2 has a perovskite solar cell efficiency of up to 10.55%, a VOC of 1.62V, and a JSC of 8.22mA / cm 2 , FF is 79.26%. These data show that Example 2 is particularly outstanding in improving battery performance.

[0069] Conclusion: This invention demonstrates an innovative method for preparing perovskite solar cells, the core of which is the use of lead nitrate (Pb(NO3)2) for interface modification. In the preparation process of the present invention, Pb(NO3)2 is used as a modifier to promote the formation of CsPbBr3 phase by passivating the defects of the perovskite layer, thereby significantly improving the crystal quality of the perovskite film. This improvement leads to fewer grain boundaries and defects, significantly reducing the recombination of carriers in the perovskite solar cell and enhancing the photovoltaic performance of the cell.

[0070] In addition, the introduction of Pb(NO3)2 also improves the energy level arrangement of the perovskite solar cell, significantly reduces the density of interface defect states, improves the extraction and transmission efficiency of carriers, and effectively inhibits charge recombination. The perovskite thin film battery prepared by the spin coating method of the present invention ultimately achieves a significant increase in the carrier recombination lifetime, thereby inhibiting charge recombination and enhancing charge extraction.

[0071] The highly efficient and stable perovskite solar cells prepared by the above steps in this application show high open circuit voltage, short circuit current, fill factor and photoelectric conversion efficiency, and have excellent environmental stability. This shows that by modifying Pb(NO3)2 on the perovskite layer, the quality of the perovskite film can be improved and its stability under environmental conditions can be enhanced. This innovative method not only improves the performance of the battery, but also provides new possibilities for the commercial application of perovskite solar cells.

[0072] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A lead nitrate interface-modified perovskite film, characterized in that: A Pb(NO3)2 solution is spin-coated on the perovskite layer to form a Pb(NO3)2 modified layer, which is the lead nitrate interface-modified perovskite film; the spin-coating speed is 1800-2200 rpm, and the time is 25-35 s; and after the spin-coating, annealing is performed at 240-260°C for 4-10 min.

2. The lead nitrate interface-modified perovskite film according to claim 1, characterized in that: The Pb(NO3)2 solution is a Pb(NO3)2 / triethyl phosphate (TEP) solution with a concentration of 0.25-3.0 mg / mL.

3. A lead nitrate interface-modified perovskite solar cell, characterized in that: A perovskite film modified with the lead nitrate interface as claimed in claim 1 or 2.

4. A method for preparing a lead nitrate interface-modified perovskite solar cell, characterized in that: The following steps are involved: S1, pretreatment of conductive transparent substrate; S2. Preparing an electron transport layer: depositing a TiO2 thin film on the surface of a conductive transparent substrate to form an electron transport layer; S3, preparing a perovskite layer: first spin-coating a PbBr2 solution on the electron transport layer, and then spin-coating a CsBr solution to form a perovskite layer; S4, preparing a Pb(NO3)2 modified layer: spin coating a Pb(NO3)2 solution on the perovskite layer to form a Pb(NO3)2 modified layer; S5. Prepare an electrode: coat a carbon electrode on the surface of the perovskite layer.

5. The method for preparing a lead nitrate interface-modified perovskite solar cell according to claim 4, characterized in that: Step S2 is specifically as follows: depositing a 1-4 v / v% TiCl4 aqueous solution on the surface of a conductive transparent substrate at 65-75°C for 25-35 minutes, then heating to 75-85°C and continuing to deposit for 10-15 minutes, standing until the temperature drops to room temperature, successively immersing in deionized water and ethanol for cleaning, and drying, the drying speed is 3950-4050r / min, the time is 25-35s, heating at 95-105°C for 4-10 minutes, and finally calcining at 450-550°C for 50-70 minutes to obtain an electron transport layer.

6. The method for preparing a lead nitrate interface-modified perovskite solar cell according to claim 4, characterized in that: Step S3 is specifically as follows: evenly spread a 0.2-0.5 g / mL PbBr2 DMF solution on the prepared electron transport layer, spin-coat it at a rotation speed of 1800-2200 rpm for 28-32 s, and then anneal it at 90-110°C for 25-35 min to form a PbBr2 film; then, spin-coat the CsBr solution on the PbBr2 film at a rotation speed of 1800-2200 rpm, and then anneal it at 240-260°C for 4-10 min to obtain the final perovskite layer.

7. The method for preparing a lead nitrate interface-modified perovskite solar cell according to claim 4, characterized in that: Step S4 is specifically as follows: evenly spread the TEP solution of Pb(NO3)2 on the perovskite layer, spin-coat at a rotation speed of 1800-2200 rpm for 25-35 seconds, and then anneal at 240-260°C for 4-10 minutes to obtain a Pb(NO3)2 modified layer.

8. The method for preparing a lead nitrate interface-modified perovskite solar cell according to claim 4, characterized in that: Step S5 is specifically as follows: coating the carbon paste by screen printing, and then heating at 110-130° C. for 10-20 min to prepare the carbon electrode.

9. The method for preparing a lead nitrate interface-modified perovskite solar cell according to claim 4, characterized in that: In step S1, the conductive transparent substrate is a FTO conductive glass substrate.

10. The method for preparing a lead nitrate interface-modified perovskite solar cell according to claim 9, characterized in that: In step S1, the pretreatment is to use laser to etch the conductive transparent substrate so that both sides thereof are non-conductive areas.

Citation Information

Patent Citations

  • Preparation method of inorganic mixed halogen perovskite thin film and application thereof in aspect of preparing solar cell

    CN107195789A

  • Lead iodide preparation method and perovskite solar cell for taking lead iodide as raw material

    CN108550641A

  • Perovskite and molecular sieve composite material and preparation method and application thereof

    CN115806814A

  • Monocrystal lead zirconate titanate net structure as well as preparation and application thereof

    CN117702271A

  • Semiconductor device, apparatus and method for manufacturing the same

    US20040155278A1